Qafiyah and Simile in a Poem “Ashadu an Laa Imraata Illaa Anti” by Nizar Qabbani - Hanik Mahliatussikah; Himatul Istiqomah; Mohammad Jawad Habeeb al-Badrani (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This research aimed to discover the variety of qafiyah and simile in one of Nizar Qabbani’s poetry. This belonged to qualitative descriptive research with qualitative data. The primary data source was a poem under the title Asyhadu an Laa Imraata Ilaa Anti. The secondary data was previous studies about it and some references about stylistic, poem, and Nizar Qabbani. The result of this research showed that in the poem Asyhadu an Laa Imraata Ilaa Anti there were three types of qafiyah, namely: 9 of mutharraf qafiyah, 6 of mutawazi qafiyah, and 5 of murashsha’ qafiyah. There were also three types of simile, namely: 11 of mursal simile, 8 of mufashshal simile, and 3 of tamtsil simile.